Traditional and functional uses of betel leaf (Piper betle L.) pertaining to food sector: a review - Roy, Arnab; Guha, Proshanta (Journal of Postharvest Technology, 2021)
Betel leaf (Piper betle L.) is a commercial crop, which is traditionally consumed in the raw state as a mouth freshener and stimulant in Southeast Asia since antiquity. It possesses various functional and medicinal properties, such as antimicrobial, antioxidant, anti-diabetic, anti-carcinogenic etc. The leaf contains essential oil, which has a unique aroma contributing flavour and fragrance. This essential oil is a mixture of concentrated phytochemicals, among which the major components are estragole, chavicol, chavibetol, ß-cubebene, and caryophyllene. In different scientific researches, betel leaf extracts or essential oil were described for its numerous beneficial functional properties, contributed by these bioactive compounds. However, some health hazards may occur, when the leaf is consumed along with areca nut and tobacco. This review article provides an overview of the current status of betel leaf and its essential oil for its utilization as a bioactive ingredient in the food system.